Warak Ngendog as a Hybrid Cultural Symbol: Negotiating Urban Multicultural Identity in Semarang, Indonesia - Muhammad Arief Budiman; Nur Hidayat; Sri Wahyuni; Ikha Listyarini; Mei Fita Asri Untari; Murywantobroto; Heri Saptadi Ismanto (Indonesian Journal Publisher, 2026)
This study examines Warak Ngendog as a hybrid cultural symbol that reflects the negotiation of urban multicultural identity in Semarang, Indonesia. In the context of globalization and rapid urban transformation, local cultural traditions are increasingly challenged to maintain their relevance while simultaneously adapting to new social, economic, and digital environments. This research aims to analyze how Warak Ngendog embodies cultural hybridity, how it is interpreted by the community, and how it contributes to the construction of social cohesion in a multicultural urban society. A qualitative ethnographic approach was employed, involving participant observation during the Dugderan Festival, semi-structured interviews with cultural practitioners and community members, document analysis, and digital ethnography of social media representations. The data were analyzed using thematic analysis informed by cultural hybridity theory, symbolic interactionism, and urban identity studies. The findings reveal that Warak Ngendog represents a symbolic integration of Javanese, Chinese, and Arab cultural elements, functioning as a medium for expressing tolerance and intercultural harmony. The tradition has undergone transformation from a religious-cultural ritual into an urban cultural icon embedded in tourism, digital media, and commercial practices. While this transformation enhances cultural visibility and economic value, it also raises concerns regarding cultural commodification and the potential dilution of its philosophical meanings. Nevertheless, Warak Ngendog continues to play a significant role in strengthening Semarang’s urban multicultural identity and fostering collective belonging among diverse communities. This study contributes to broader discussions on cultural hybridity, urban identity, and multiculturalism by demonstrating how local cultural symbols operate as mechanisms of social integration in contemporary urban societies. It also highlights the importance of balancing cultural preservation with modernization in sustaining intangible cultural heritage.